EVALUASI STABILITAS DINDING SALURAN PADA PERENCANAAN SALURAN IRIGASI LUMBANGSARI DESA LUMBANGSARI KECAMATAN BULULAWANG - Supriyanto, Agus; Suhudi, Suhudi (Universitas Tribhuwana Tunggadewi Malang, 2019)
Landslide problems often occur in Indonesia, such as in irrigation canals, most are still in the form of land channels, which results in considerable water loss due to many leaks, so that water disputes often occur by farmers during the dry season. The channel wall landslides also impacted the silting of the irrigation channels which resulted in a non-smooth flow of water, the need for irrigation water on the DI Channel. Lumbangsari (252 Ha) cannot meet the water needs in the rice fields. One of the ways used to control the stability of the soil so that it does not slide is to build a retaining wall on the channel. Planning the channel wall located in DI. Lumbangsari (252 Ha), Lumbangsari Village, Bululawang District, Malang Regency. In this evaluation plan, data is taken directly through direct surveys at locations and using maps of soil types. In order for the building to function properly, the stability of the building must also be planned as well as possible, therefore, the stability of the channel wall is analyzed with the danger of rolling (bolting) and gliding under normal water conditions without earthquakes, double earthquakes and flood water conditions without earthquakes , with earthquakes analyzed using Rankine formulas. The result is SFsliding 1.85> 1.5 and 1.85> 1.5, SFbolters 1.64> 1.5 and 1.64> 1.5 (for normal conditions without earthquakes and with earthquakes) and SFsliding 2.05 > 1.5 and 2.03> 1.5, SFbolters 1.67> 1.5 and 1.66> 1.5 (for flood conditions without and with earthquakes), the situation is safe. In this study the budget plan for the cost of the channel wall is Rp. 52,781,008.28.